Analysis of Rhodamin B in Lipstick Preparations in Padangsidimpuan City by Thin Layer Chromatography (TLC) Method - Harahap, Susilawati; Lubis, Lathipah Hannah; Harahap, Minah Iryanti (Formosa Journal of Science and Technology, 2024)
Rhodamin B is a synthetic dye in the form of a crystalline powder, green or reddish-purple, odorless, and in solution will be bright red with fluorescence or fluorescence. Rhodamin B is commonly used as a dye in the textile and papermaking industries. Rhodamin B can cause irritation in short-term exposure and has carcinogenic effects. This study aims to find out whether there is Rhodamin B in lipsticks circulating in the Padangsidimpuan City market. Samples were taken by purposive sampling and 5 red samples were obtained. To identify the presence of Rhodamin B, a thin-layer chromatography method was used using eluene as the phase of motion, namely methanol, ethyl acetate, ammonia (50:20:25) and a 254 nm UV lamp The results of the study showed that out of 5 lipstick samples identified, there was one lipstick sample that was identified as containing Rhodamin B.